SEROPREVALENCE AND RISK FACTORS OF SPECIFIC TOXOPLASMA GONDII ANTIBODY AMONG PREGNANT WOMEN - AHMED, AHMED J.; ZEEBAREE, BAYAR K.; KHANAMIR, RAMADHAN A. (Journal of Duhok University, 2020)
Toxoplasmosis during pregnancy has an adverse effect on pregnant women, fetus and neonatal. The infection is generally asymptomatic but can cause severe effect on the fetus and immunocompromised women. Control study conducted on 77 pregnant women categorized according to the risk factors influencing toxoplasmosis infection. Specific anti Toxoplasma gondii IgG and IgM were evaluated using Enzyme-linked immunosorbent assay (ELISA) test kits. Among 77 pregnant women, (57.1%) women had toxoplasmosis, seropositive for latent infection with specific Toxoplasma gondii immunoglobulin G (IgG) antibodies were (54.54 %), whereas acute infection immunoglobulin M (IgM) were only in (2.59 %) cases. The seroprevalence of Toxoplasma was higher in older pregnant women (> 60%) than younger ones (<50%). The specific IgG antibody was higher in pregnant women working in farms (65.7 vs 45.23; P=0.053). Also, the seropositive IgG antibody was low in the first trimester and high in rural areas. Pregnant women need to educate more about toxoplasmosis and prevention to exposure in order to reduce the risk of congenital toxoplasmosis.